The use of antibodies in the prophylaxis and treatment of infections - Peter J Lachmann (Emerging Microbes and Infections, 2012)
The use of antibodies to provide passive immunity to infections has a long history. Although the coming of antibiotics greatly reduced its use for bacterial infections, it is still widely used for a variety of purposes which are reviewed here. The use of animal antisera gave way to the use of human convalescent serum as a source of antibodies and more recently human and monoclonal antibodies have become widely used, not just providing passive immunity but as therapeutic agents. The current uses of antibody therapy are discussed as are the problems of antibody-mediated immunopathology and how this can be avoided. More recent developments include the making of monoclonal antibodies that react with cross-reacting determinants on flu viruses. Such antibodies are not usually made following infection and they provide a very promising approach to providing passive immunity that will be effective against a variety of different strains of the flu virus. It is also pointed out that passive immunotherapy can act as a surrogate vaccine providing that the subject gets infected while protected by the passive antibodies. Finally, there is a section on the possible use of oral antibodies given as food to prevent diseases such as infantile gastroenteritis.